The Strategic Role of Innovation as a Mediator Between Internal Firm Factors and Value Creation: : A Study of the Indonesian Manufacturing Industry - Prihat Assih; Diyah Sukanti Cahyaningsih; Kanitsorn Terdpaopong (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction/Main Objectives: This study analyzes the role of innovation in bridging factors that influence firm value. As is known, COVID-19 has triggered manufacturing companies to innovate both processes and products. Methods: This study places the innovation variable as an intervening variable to examine whether companies with adequate profitability, assets, managerial ownership, and determinants of R&D activities can drive firm value. The sample in this study was 132 manufacturing companies with an observation period of 2021-2024. Finding/Results: The results of this study show that the role of managerial ownership influences corporate innovation. Firm size hurts innovation, and the ability to generate profits in period t-1 can drive innovation in period t. Firm value is proven to be influenced by managerial ownership, size, profitability, and innovation. Innovation can also act as an intervening variable. Conclusions: This study contributes a discourse that the role of innovation in manufacturing companies is quite significant. Government encouragement can increase R&D activities. Thus, manufacturing companies should consider R&D activities, which are a positive signal for investors.